Norway : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Selected Issues paper presents an assessment of Norway's inflation targeting framework. It describes the institutional framework, and reviews accountability and transparency of the central bank as well as its communication with the public. The paper discusses the design of the framework, and the monetary transmission. It concludes that the institutional framework is appropriate for successful implementation of monetary policy. The new framework provides a more flexible monetary regime that is consistent with Norway's overall economic policy framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet